Exploring the nature of interprofessional collaboration and family member involvement in an intensive care context. Issue 1 (January 2014) - Paradis, Elise; Reeves, Scott; Leslie, Myles; Aboumatar, Hanan; Chesluk, Ben; Clark, Philip; Courtenay, Molly; Franck, Linda; Lamb, Gerri; Lyndon, Audrey; Mesman, Jessica; Puntillo, Kathleen; et al.
Abstract Little is known about the nature of interprofessional collaboration on intensive care units (ICUs), despite its recognition as a key component of patient safety and quality improvement initiatives. This comparative ethnographic study addresses this gap in knowledge and explores the different factors that influence collaborative work in the ICU. It aims to develop an empirically grounded team diagnostic tool, and associated interventions to strengthen team-based care and patient family involvement. This iterative study is comprised of three phases: a scoping review, a multi-site ethnographic study in eight ICUs over 2 years; and the development of a diagnostic tool and associated interprofessional intervention-development. This study's multi-site design and the richness and breadth of its data maximize its potential to improve clinical outcomes through an enhanced understanding of interprofessional dynamics and how patient family members in ICU settings are best included in care processes. Our research dissemination strategy, as well as the diagnostic tool and associated educational interventions developed from this study will help transfer the study's findings to other settings.